1981
DOI: 10.1042/bj1940721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micromolar concentrations of free Ca2+ ions on pyruvate dehydrogenase interconversion in intact rat heart mitochondria

Abstract: 1. The mitochondrial content of active (dephospho) pyruvate dehydrogenase (PDHA) was found to be severalfold higher at an extramitochondrial Ca2+ concentration of 2 microM (pCa6) than at pCa7. The nature of the respiratory substrate did not affect this finding. 2. This Ca2+-dependence was shown in state-4 and 50%-state-3 conditions [see Chance & Williams (1956) Adv. Enzymol. 17, 65-134], but was absent in the presence of excess ADP (state 3). 3. Na+ and Mg2+ ions shifted the pCa value required for a maximal PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
36
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 54 publications
6
36
1
Order By: Relevance
“…This approach, as originally proposed by Grynkiewicz et al (1985), would minimize problems due (c) (Hansford & Cohen, 197-;Hansford, 1981), but also exploit the indo-1 technique to measure the important parameter [Ca2+1m. Addition of Ruthenium Red, and inhibition of the Ca2+ uniporter (Moore, 1971), results in a rapid decrease in fluorescence, corresponding to loss of Ca2+ from the mitochondrial matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach, as originally proposed by Grynkiewicz et al (1985), would minimize problems due (c) (Hansford & Cohen, 197-;Hansford, 1981), but also exploit the indo-1 technique to measure the important parameter [Ca2+1m. Addition of Ruthenium Red, and inhibition of the Ca2+ uniporter (Moore, 1971), results in a rapid decrease in fluorescence, corresponding to loss of Ca2+ from the mitochondrial matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Each of these dehydrogenase systems is present within the permeability barrier of the mitochondrial inner membrane, leading (Sheu & Fozzard, 1982;McCormack & England, 1983), would elicit enhanced dehydrogenase activity, and enhanced energy transduction by oxidative phosphorylation. Evidence in favour of this proposal has been recently reviewed (Denton & McCormack, 1985;Hansford, 1985).Although there is good agreement on the relationship between the fraction of pyruvate dehydrogenase existing in the active dephosphorylated form (PDHA; see reviews by Reed, 1981;Wieland, 1983) in isolated cardiac mitochondria and the concentration of free ionized Ca2" ([Ca2+]O) in the suspending medium (Hansford & Cohen, 1978;Hansford, 1981) al., 1982;Hansford & Castro, 1982), and the insertion of the metallochromic indicator Arsenazo III into the mitochondria by a permeabilization/resealing protocol (Hayat & Crompton, 1987). The precision of the 'nullpoint' technique is limited by the small absorbance changes seen with the extramitochondrial metallochromic indicator when mitochondrial Ca2" loads low enough to be of relevance to dehydrogenase regulation are investigated, whereas the permeability/resealing protocol may, theoretically at least, perturb the matrix composition, especially with respect to metal ions and low-molecular-mass cofactors.…”
mentioning
confidence: 99%
“…In the presence of both Na+ and Mg2 +, half-maximal activation was observed at about 0.5 pM-Ca2 +, and thus it could be argued that changes in cytoplasmic [Ca2 + ] within the physiological range (see Marban et al, 1980) would be expected to result in changes in intramitochondrial metabolism in the intact heart . These findings led us to propose that hormones and neurotransmitters which act by increasing the concentration of cytoplasmic Ca2 + could also influence intramitochondrial oxidative metabolism through increases in the intramitochondrial concentration of Ca2 +, and hence activation of the above enzymes , 1981. Strong evidence for this view has been obtained in subsequent studies on the effects of P-adrenergic agonists on the rat heart (McCormack & England, 1983;.…”
mentioning
confidence: 68%
“…Studies, mainly with rat heart, have indicated tissues (see , 1981 ,1978aMcCormack & Denton, 1979,1981b dehydrogenase activity can be demonstrated withthe concentration of effector required for a half-maximal in coupled rat heart mitochondria exposed to response.…”
mentioning
confidence: 99%
See 1 more Smart Citation